Knowledge, attitude, practice and determining factors regarding nutrition during pregnancy among females of rural Punjab - ., Sanyogita; Singh, Tejbir; Deepti, S. S. (International Journal Of Community Medicine And Public Health, 2019)
Background: The health of a pregnant mother and her nutritional status can influence the health and survival of the growing foetus because of the biological link between them. This study was conducted to assess the knowledge, attitude, practice and determining factors regarding nutrition during pregnancy among females of rural Punjab. Methods: 359 mothers of 2 months to 24 months old children were selected from Verka block of district Amritsar using stratified random sampling technique. Data was collected using a semi structured and pretested questionnaire. Analysis was done using frequency distribution, simple percentages and inferential statistics of chi-square was used to test hypothesis at 5% level of significance. Results: Findings reveal that 81.1% of respondents stressed on adding extra diet during pregnancy out of which only 77.3% of mothers actually added or increased one or more food items. Place of residence, education and parity were significantly associated with knowledge regarding diet increase during pregnancy. Fear of caesarean section and difficult labour were the main reasons given for not adding extra diet during pregnancy. Conclusions: The study however suggests that there is a need for educating the mothers regarding importance of diet during pregnancy.